Meyerson-Phenomenon hides a nevus flammeus - Simon, Vera; Hartschuh, Wolfgang; Flux, Katharina (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
Facial eczema is a common disease in daily dermatological practice. The cause of facial eczema is often atopic dermatitis or allergic contact dermatitis. Usually, the eczema resolves with correct topical treatment and by avoiding allergic trigger factors. A 49-year-old woman presented with persistent eczema on her forehead which recurred over decades despite correct topical therapy. A skin biopsy revealed the astonishing diagnosis of a nevus flammeus with an overlying eczema known as the Meyerson phenomenon. The Meyerson phenomenon is often described in children with nevi flammei suffering from atopic dermatitis - in adults the phenomenon is rarely recognized as a reason for eczema. We show the interesting case of an adult woman with the Meyerson phenomenon on a nevus flammeus and discuss the possible pathomechanisms.
First published: 13 August 2010
Gesehen am 14.10.2022